Role of in-flight temperature and velocity of powder particles on plasma sprayed hydroxyapatite coating characteristics - Cizek, Jan (2013)
This paper presents a systematic research on the process of thermal spraying of HA encompassing all stages of layer deposition: powder production and characterization (optimized production led to spherical 39.90 ± 10.61 μm powder with 0.0% content of tri-calcium phosphate [TCP] or tetra-calcium phosphate [TTCP] phases), plasma jet properties influence on the in-flight powder properties (major influence of spray distance factor), the influence of the in-flight temperature and velocity of hydroxyapatite powder particles (ranges of 2294 K–2708 K and 152 m·s−1–291 m·s−1) on the final characteristics of the deposited coatings. Six combinations of the system parameters leading the low-medium-high in-flight properties were selected and the respective coatings were investigated, with some data in contradiction to previously published results. It was found that the temperature of the particles plays a critical role for the development of detrimental CaO (content increase of up to 14.6%) and metastable TTCP (up to 49.5%) phases in the coatings. Particle in-flight velocity was found to influence the open porosity of the coatings (8.8%–27.9%) and has an impact on the micro-hardness and moduli of the coatings (relative differences of up to 2.8×). Joint incidence of both in-flight properties was found to significantly influence the microstructure of the coatings and its respective surface roughness levels (Ra = 7.4–19.4 μm). The morphology of impinging splats was found to be influenced by both the in-flight velocity (dominant factor) and temperature (secondary factor) of the HA particles.